Hubungan Kematangan Karir Dan Komitmen Kerja Pada Karyawan Tetap - Apipah (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
Background: Commitment is very necessary, even though in reality not all employees can show their commitment to the company, especially in Indonesia. Objective: This study aims to empirically examine the relationship between career maturity and work commitment in permanent employees. This research is expected to contribute to psychology, especially in the field of industrial and organizational psychology, and can be used as a guideline for further research. Method: The method in this study uses a correlational quantitative method. The sampling technique used in this study uses purposive sampling. The sample in this study is 75 permanent employees who work for a company or agency with a minimum working period of two years. The measurement of the scale of work commitment in this study uses the Three Component Organizational Commitment Scale and the measurement of the career maturity scale uses the Career Maturity Inventory Form C (CMI Form C) which is compiled using the Likert scale. The research data was analyzed using the Product Moment correlation technique. Result: Based on the results of the analysis that has been carried out, a correlation coefficient value of 0.795 and a significance value of 0.000 were obtained. Conclusion: These results show that in this study the accepted hypothesis is that there is a very significant positive relationship between career maturity and work commitment in permanent employees.